Highly-sensitive graphene-based flexible pressure sensor platform - Muhammad Aniq Shazni,; Lee, Mai Woon; Lee, Hing Wah (Penerbit Universiti Kebangsaan Malaysia, 2017)
In this work, graphene has been utilized as the sensing material for the development of a highly-sensitive flexible pressure sensor platform. It has been demonstrated that a graphene-based pressure sensor platform that is able to measure pressure change of up to 3 psi with a sensitivity of 0.042 psi-1 and a non-linearity of less than 1% has been accomplished. The developed device, which resides on a flexible platform, will be applicable for integration in continuous wearables health-care monitoring system for the measurement of blood pressure.